Angiotensinogen as a risk factor for essential hypertension in Japan. - Hata, A (1994)
A common molecular variant of angiotensinogen (AGT), the precursor of the potent vasoactive hormone angiotensin II, has been incriminated as a marker for a genetic predisposition to essential hypertension in Caucasians (Jeunemaitre, X., F. Soubrier, Y. V. Kotelevtsev, R. P. Lifton, C. S. Williams, A. Charru, S. C. Hunt, P. N. Hopkins, R. R. Williams, J. M. Lalouel, and P. Corvol. 1992. Cell. 71:169-180). We now show that the same variant, T235, is associated with essential hypertension in Japanese patients. The observation of this association in a distinct, ethnically homogeneous population further substantiates an involvement of angiotensinogen in the pathogenesis of essential hypertension and has physiological, epidemiological, and evolutionary implications.